KONTROVERSI JALAN KAKI KE BAITULLAH SAMBIL LIVE STREAMING DI MEDIA SOSIAL (KAJIAN ISTITHA'AH HAJI/UMROH PERSPEKTIF HUKUM ISLAM) - Akhmad Rudi Maswanto; Firma Yudha (International Conference on Humanity Education and Society (ICHES), 2026)
The digital era has birthed a new phenomenon in religious practices: performing the Hajj or Umrah pilgrimage on foot while broadcasting the journey through live streaming on social media platforms like TikTok. This phenomenon is often accompanied by online donation solicitations from viewers, triggering public controversy and the label of "digital begging." This research aims to analyze this phenomenon from an Islamic law perspective, specifically regarding its relevance to the concept of istitha’ah (capability) as a mandatory requirement for Hajj, while also examining the dimensions of worship ethics in the digital space. This study employs a qualitative approach with a juridical-normative method and library research. Data are analyzed by referring to classical and contemporary fiqh (Islamic jurisprudence) literature concerning the requirements of Hajj and digital muamalah ethics. Findings: The results indicate that the practice of traveling to the Baitullah by relying on social media donations does not meet the criteria for independent financial istitha’ah according to the majority of scholars. Furthermore, such actions potentially reduce the essence of the sanctity of worship, as they are susceptible to elements of riya’ (showing off), sum’ah (seeking popularity), and the exploitation of religious symbols for personal material gain. This article concludes that while technology provides new spaces for expression, a sincere and pure intention remains the fundamental basis of Islamic law in performing Hajj. Massive religious education is necessary to enhance digital ethical awareness so that the sanctity of worship remains preserved amidst the tides of modernity.